Surgical correction for scimitar syndrome by right thoracotomy and direct anastomosis in children. Issue 1 (22nd March 2021) - Cheng, Wei; Li, Zhiqiang; Zhu, Yaobin; Ding, Nan; Yan, Daole; Yi, Hanlu
ABSTRACT: Importance: Scimitar syndrome (SS) is a rare type of congenital heart disease characterized by total or partial anomalous venous drainage of the right lung to the inferior vena cava. However, the surgical repair techniques for SS vary according to patients' anatomical and pathological features. Objective: This study was performed to analyze the mid‐term results of a less invasive surgical correction technique for SS in children. Methods: Eleven patients with SS who underwent surgical repair from January 2012 to March 2020 were retrospectively analyzed. The anomalous scimitar vein (SV) was directly reimplanted to the left atrium, and the concomitant atrial septal defect was simultaneously repaired with cardiopulmonary bypass. Results: Three male and eight female patients were included in the study. Their mean age was 3.1 ± 1.3 years, and their mean body weight was 12.8 ± 3.0 kg. Most patients had symptoms, such as upper respiratory tract infection, dyspnea, and recurrent pneumonia, and two patients had pulmonary hypertension. None of the 11 patients who underwent direct SV reimplantation by right thoracotomy developed bleeding, arrhythmia, heart failure, or perioperative death, and no patients required reoperation during a mean follow‐up period of 36.6 ± 15.2 months. Postoperative echocardiography revealed no restenosis or obstruction of the anastomosis in any patients. Interpretation: Surgical repair for SS by right thoracotomy and direct anastomosis of the SV to the posterior wall of the left atrium is safe and effective, with good long‐term patency of the reimplanted SV and a low mortality rate.